2017
DOI: 10.47102/annals-acadmedsg.v46n4p124
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Minimally Invasive and Conventional Open Surgery Approach in the Treatment of Lumbar Stenosis: A Systematic Review and a Meta-Analysis

Abstract: Introduction: Minimally invasive surgery (MIS) is increasingly used in the treatment of lumbar stenosis. However, it is still not clear if the employment of minimally invasive surgical techniques can achieve superior clinical outcomes compared to standard open laminectomy. Materials and Methods: An extensive literature review regarding the clinical outcome, safety, and efficiency of MIS and standard open surgery (OS) in the treatment of lumbar stenosis was conducted on Medline, Cochrane, EMBASE, and Google Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…Chang et al also found no significant difference in ODI and operation time between MIS and conventional open surgery. 14 Wang et al, 15 however, found a significantly shorter operating time for MI-TLIF (127 ± 25 minutes) compared with open TLIF (168 ± 37 minutes) in obese patients. Concerning radiation exposure, most of the studies have shown significantly longer radiation exposure times during MISS surgery (range: 45.3–106 seconds) compared to conventional open procedures (range: 24–39 seconds).…”
Section: Discussionmentioning
confidence: 95%
“…Chang et al also found no significant difference in ODI and operation time between MIS and conventional open surgery. 14 Wang et al, 15 however, found a significantly shorter operating time for MI-TLIF (127 ± 25 minutes) compared with open TLIF (168 ± 37 minutes) in obese patients. Concerning radiation exposure, most of the studies have shown significantly longer radiation exposure times during MISS surgery (range: 45.3–106 seconds) compared to conventional open procedures (range: 24–39 seconds).…”
Section: Discussionmentioning
confidence: 95%
“…However, there is no doubt about its minimally invasive nature. In the treatment of degenerative lumbar spine disease, the currently accepted clinical goals are minimal trauma, optimal neurological decompression and maximum preservation of the lumbar segmental motion [ 53 ]. In this context, PES is gradually gaining acceptance among clinicians and expanding the scope of its clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Сравнение результатов микроэндоскопической декомпрессии у пациентов с симптоматическим стенозом и сопутствующей умеренной деформацией поясничного отдела позвоночника с данными о естественном прогрессировании деформации позволяет сделать вывод об отсутствии отрицательного влияния локальной декомпрессии на прогрессирование деформации [5]. Это выглядит логичным, учитывая основную мотивацию применения минимально инвазивных технологий в виде сохранения мышечного каркаса и задних элементов позвоночного столба, включая дугу, межостистые отростки и связочный аппарат [9][10][11]23]. Сохранение целостности этих структур позволяет предотвратить развитие ятрогенной послеоперационной нестабильности [24].…”
Section: Discussionunclassified
“…В настоящее время большое распространение в лечении СПС получили минимально инвазивные технологии, которые обладают рядом преимуществ в виде ограниченного повреждения мягких тканей, низкой кровопотери, менее выраженного послеоперационного болевого синдрома, сокращения сроков госпитализации, непродолжительного восстановительного периода [9][10][11]. Ряд авторов [5,8,12] указывают также на предпочтительность использования минимально инвазивных вмешательств при сочетании СПС и деформации позвоночника.…”
unclassified